THE DEVELOPMENT OF ENGLISH LEXICON AS THE INFLuENCE OF SOCIAL CHANGES - Albertus Suwardi (Soegijapranata Catholic University, 2009)
This paper describes and explains the development of English in general and especially the English lexicon as the influence of social changes from time to time. We know that English can be divided into three periods; the period from 450 to 1100 is known as Old English,from 1100 to 1500, is known as Middle English, and the last, from 1500 up to now is known as Modern English. From the three periods it is found that English always develops and changes. The English of each period is different from the English of other periods.